A Rose by Any Other Name: The Long Intricate History of Localized Aggressive Periodontitis - Daniel H. Fine; Helen Schreiner; Scott R. Diehl (Pathogens, 2024)
This review addresses the recent World Workshop Consensus Conference (WWCC) decision to eliminate Localized Aggressive Periodontitis (LAgP) in young adults as a distinct form of periodontitis. A “Consensus” implies widespread, if not unanimous, agreement among participants. However, a significant number of attendees were opposed to the elimination of the LAgP classification. The substantial evidence supporting a unique diagnosis for LAgP includes the (1) incisor/molar pattern of disease, (2) young age of onset, (3) rapid progression of attachment and bone loss, (4) familial aggregation across multiple generations, and (5) defined consortium of microbiological risk factors including Aggregatibacter actinomycetemcomitans. Distinctive clinical signs and symptoms of LAgP are presented, and the microbial subgingival consortia that precede the onset of signs and symptoms are described. Using Bradford–Hill guidelines to assess causation, well-defined longitudinal studies support the unique microbial consortia, including A. actinomycetemcomitans as causative for LAgP. To determine the effects of the WWCC elimination of LAgP on research, we searched three publication databases and discovered a clear decrease in the number of new publications addressing LAgP since the new WWCC classification. The negative effects of the WWCC guidelines on both diagnosis and treatment success are presented. For example, due to the localized nature of LAgP, the practice of averaging mean pocket depth reduction or attachment gain across all teeth masks major changes in disease recovery at high-risk tooth sites. Reinstating LAgP as a distinct disease entity is proposed, and an alternative or additional way of measuring treatment success is recommended based on an assessment of the extension of the time to relapse of subgingival re-infection. The consequences of the translocation of oral microbes to distant anatomical sites due to ignoring relapse frequency are also discussed. Additional questions and future directions are also presented.